IMF conditionality: Theory and evidence - Axel Dreher (ETH Zurich, KOF Swiss Economic Institute, 2008)
This article analyzes whether and to what extent reliance on conditionality is appropriate to guarantee the revolving character of Fund resources. The paper presents theoretical arguments in favour of conditionality, and those against the use of conditions. It summarizes the track record of program implementation and discusses the evidence of factors determining implementation. Whether proponents or critics of conditionality can be supported by existing data analysis is also investigated, as is the success of conditionality in terms of outcomes. The final section draws policy implications.
Keywords: 330; IMF; conditionality; compliance; implementation; Anpassungsprogramm des IWF; Einführung; Wirkungsanalyse; Welt